Facile synthesis of Vulcan XC-72 nanoparticles-decorated halloysite nanotubes for the highly sensitive electrochemical determination of niclosamide. (1st May 2021) - Zhao, Hongyuan; Chang, Yuqi; Liu, Runqiang; Li, Bo; Li, Fang; Zhang, Fulong; Shi, Mingwang; Zhou, Lin; Li, Xiaoguang
Highlights: Vulcan XC-72@halloysite composite was prepared using ultrasound. A modified sensor was fabricated to detect the niclosamide. Vulcan XC-72@halloysite composite had a synergistic effect. A low detection limit of 3.5 nM was achieved. Good niclosamide determination effect was obtained in food samples. Abstract: We report a scalable and controllable ultrasound-assisted strategy for the preparation of Vulcan XC-72 nanoparticles-decorated halloysite nanotubes (HNTs@VXC-72), which was applied to modify glassy carbon electrode (GCE) for the highly sensitive electrochemical determination of niclosamide (NA). For the HNTs@VXC-72 nanocomposite, VXC-72 nanoparticles with excellent electrical conductivity and good dispersing property contributed to the formation of the interconnected conductive network; HNTs possessed good adsorption performance and promoted the electrochemical redox reaction. The research results showed that the combination of VXC-72 nanoparticles and HNTs produced the effect of synergistic enhancement. The HNTs@VXC-72/GCE sensor could show a relatively low detection limit of 3.28 nM in the great linear NA concentration range of 0.01–1 µM. When used for the NA determination in food samples, the HNTs@VXC-72/GCE sensor exhibited good practical feasibility with low RSD and acceptable recoveries, which provided a promising NA determination approach to ensure food safety.